2010
DOI: 10.1111/j.1365-2966.2010.17801.x
|View full text |Cite
|
Sign up to set email alerts
|

Extreme active galactic nucleus feedback and cool-core destruction in the X-ray luminous galaxy cluster MACS J1931.8−2634

Abstract: We report on a deep, multiwavelength study of the galaxy cluster MACS J1931.8−2634 using Chandra X-ray, Subaru optical and Very Large Array 1.4-GHz radio data. This cluster (z = 0.352) harbours one of the most X-ray luminous cool cores yet discovered, with an equivalent mass, cooling rate within the central 50 h −1 70 kpc is ∼700 M yr −1 . Unique features observed in the central core of MACS J1931.8−2634 hint to a wealth of past activity that has greatly disrupted the original cool core. The X-ray and optical … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
97
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(106 citation statements)
references
References 89 publications
9
97
0
Order By: Relevance
“…The jets are known to influence the conditions of the surrounding interstellar medium (ISM). Signatures of this are seen at both large (Nesvadba 2009;Ehlert et al 2011;McNamara & Nulsen 2012) and small (Rosario et al 2010a,b;Morganti et al 2013) scales in accordance with simulations (Mellema et al 2002;Fragile et al 2004;Wagner & Bicknell 2011). Recent studies of the interaction between a jet and its surrounding ISM have brought a number of surprises.…”
Section: Introductionmentioning
confidence: 88%
“…The jets are known to influence the conditions of the surrounding interstellar medium (ISM). Signatures of this are seen at both large (Nesvadba 2009;Ehlert et al 2011;McNamara & Nulsen 2012) and small (Rosario et al 2010a,b;Morganti et al 2013) scales in accordance with simulations (Mellema et al 2002;Fragile et al 2004;Wagner & Bicknell 2011). Recent studies of the interaction between a jet and its surrounding ISM have brought a number of surprises.…”
Section: Introductionmentioning
confidence: 88%
“…Specifically, the increasing peaky fraction implies that cool core disruption is more efficient in less massive halos. There are several known examples of cool cores being destroyed by ram pressure stripping as they oscillate (slosh) about the bottom of the cluster potential following a merger (Markevitch et al 2000, Mazzotta et al 2001, Million et al 2010, Ehlert et al 2011, Ichinohe et al 2014, a process also observed in hydrodynamic simulations (e.g. Burns et al 2008, ZuHone et al 2011.…”
Section: Trends With Redshift Temperature and Parent Samplementioning
confidence: 99%
“…There is increasing evidence from radio and X-ray observations of local clusters that the formation of bubbles due to radio jets associated to the central AGN may effectively satisfy the energy balance between cooling and heating in cool-core regions (Blanton 2001;Ehlert et al 2011). In this respect, the radio luminosity of the central galaxy provides an important link between the black hole activity and the state of the intracluster medium.…”
Section: Introductionmentioning
confidence: 99%